Government Budgeting and Expenditure Controls : Theory and Practice - Premchand, A. (Washington, D.C. : International Monetary Fund, 1989)
This book, written by A. Premchand, offers a comprehensive review of fiscal policies and their implications for budgeting and expenditure controls. It provides an in-depth discussion of techniques, procedures, and processes of budgeting with illustrative material drawn from the experiences of industrial and developing countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet